2016
DOI: 10.1039/c6ra08700k
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of CoxMn3−xO4 nanoparticles with a tunable composition and size for high performance lithium-ion batteries

Abstract: Preparation of CoxMn3−xO4 nanoparticles using bimetallic coordination-polymer precursors, and a case study of MnCo2O4 for LIBs, suggesting an optimal size for improved capacity retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…[3][4][5] Graphite is widely used as a commercial anode material for LIBs, however, during the charge-discharge process, it will form an intercalation compound LiC 6 , which provides a relatively low theoretical capacity of 372 mA h g À1 . [6][7][8] Sn-based composites, 9,10 Si-based composites, 11,12 P-based composites 13,14 and transition metal oxides 15,16 have been extensively studied as alternative anode materials for LIBs because of their higher energy density compared with graphite and they also possess good ability to react with large amounts of Li per formula unit. For instance, tin sulfide (SnS) nanorods were prepared and used as an anode electrode with a good reversible capacity of 750 mA h g À1 at a current density of 160 mA g À1 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Graphite is widely used as a commercial anode material for LIBs, however, during the charge-discharge process, it will form an intercalation compound LiC 6 , which provides a relatively low theoretical capacity of 372 mA h g À1 . [6][7][8] Sn-based composites, 9,10 Si-based composites, 11,12 P-based composites 13,14 and transition metal oxides 15,16 have been extensively studied as alternative anode materials for LIBs because of their higher energy density compared with graphite and they also possess good ability to react with large amounts of Li per formula unit. For instance, tin sulfide (SnS) nanorods were prepared and used as an anode electrode with a good reversible capacity of 750 mA h g À1 at a current density of 160 mA g À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the characteristic absorption peak at 1427 and 847 cm −1 was associated with C=C ring stretching and the benzene ring out‐of‐plane vibration [27] . It is noted that the characteristic bands of the nonionized carboxyl groups (ν O−H , 3086 cm −1 ; ν C=O , 1654 cm −1 ) are not observed for the MOF sample, while new absorption bands appear at 1549 cm −1 and 1420 cm −1 , which correspond to the asymmetric and symmetric stretching vibrations of carboxylate groups, respectively [28] . Furthermore, the FTIR spectra showed the specific vibration mode of in‐plane C−O−H bending and hydrogen‐bond stretching at around 3378 cm −1 , which could be attributed to methanol molecules inside 1D channels within the honeycomb structure [29] .…”
Section: Resultsmentioning
confidence: 95%
“…[27] It is noted that the characteristic bands of the nonionized carboxyl groups (ν OÀ H , 3086 cm À 1 ; ν C=O , 1654 cm À 1 ) are not observed for the MOF sample, while new absorption bands appear at 1549 cm À 1 and 1420 cm À 1 , which correspond to the asymmetric and symmetric stretching vibrations of carboxylate groups, respectively. [28] Furthermore, the FTIR spectra showed the specific vibration mode of in-plane CÀ OÀ H bending and hydrogen-bond stretching at around 3378 cm À 1 , which could be attributed to methanol molecules inside 1D channels within the honeycomb structure. [29] In short, these results distinctly confirmed that Cu 2 + centers have been coordinated with the 2,5-dihydroxyterephthalic acid ligand successfully.…”
Section: Resultsmentioning
confidence: 97%
“…435,436 Silicon anodes with a very large capacity of 3580 mAh g À1 (Li 15 Si 4 ) are suggested as an alternative, but large volume expansion during charging and discharging poses a serious safety problem. 437 As alternatives to the graphite anode materials, tin (Sn)-based composites, 438,439 phosphorous (P)-based composites, 440 and transition metal oxides (TMO) 441,442 have been studied, which have a higher capacity and superior rate capability compared to graphite. These materials suffer from significant volume changes upon the lithiation/delithiation 428 Copyright 2012, American Chemical Society processes, however, causing particle agglomeration or structural collapse during cycling, which eventually leads to a rapid capacity loss.…”
Section: Lithium-ion Batterymentioning
confidence: 99%